2012
DOI: 10.3354/dao02506
|View full text |Cite
|
Sign up to set email alerts
|

Dermatitis and systemic mycosis in lined seahorses Hippocampus erectus associated with a marine-adapted Fusarium solani species complex pathogen

Abstract: During a 4 mo epizootic, 100% of 152 lined seahorses Hippocampus erectus in 3 separate groups died while in quarantine following shipment to a public aquarium. Twelve animals with skin depigmentation and ulceration were received by the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 37 publications
3
35
0
Order By: Relevance
“…was isolated from seawater in a mangrove habitat (Miao et al 2006). Interestingly, Fusarium is a widespread genus in marine environments, where it has been associated with fungal diseases of marine animals caused by F. solani (Salter et al 2012;Hatai 2012), and is known to play a role in anaerobic denitrification in marine environments (Richards et al 2012). The large number of taxa also found in other marine substrates and hosts (Table 3) suggests that the fungal community in sponges might have been acquired through horizontal transmission.…”
Section: Associations Of Fungal Isolates With Other Organisms and Thementioning
confidence: 96%
“…was isolated from seawater in a mangrove habitat (Miao et al 2006). Interestingly, Fusarium is a widespread genus in marine environments, where it has been associated with fungal diseases of marine animals caused by F. solani (Salter et al 2012;Hatai 2012), and is known to play a role in anaerobic denitrification in marine environments (Richards et al 2012). The large number of taxa also found in other marine substrates and hosts (Table 3) suggests that the fungal community in sponges might have been acquired through horizontal transmission.…”
Section: Associations Of Fungal Isolates With Other Organisms and Thementioning
confidence: 96%
“…Loss of habitat, changing climate and human harvesting threaten wild populations of many syngnathid species (Vincent, Foster, & Koldewey, ). In captivity, syngnathids are susceptible to infectious diseases including mycobacteriosis, scuticocilliatosis, phaeohyphomycosis, fusariosis and vibriosis (Bonar et al., ; LePage et al., ; Nyaoke et al., ; Salter et al., ). Aside from water quality‐related issues, particularly gas bubble trauma, non‐infectious diseases, such as neoplasia, are less commonly reported in syngnathids.…”
mentioning
confidence: 99%
“…Fusarium sp. FSSC 12 has been reported to cause mycotic infections in humans (16) and in a number of captive marine animals, including a recent epizootic at a public aquarium in the United States that resulted in 100% mortality of lined seahorses (Hippocampus erectus) (19), cutaneous lesions in scalloped hammerhead sharks from Japan in a public aquarium in Hong Kong (Sphyrna lewini) (14), black gill disease of kuruma prawn (Penaeus japonicas) in Japan (25), and fatal mycotic infections of lobsters in Australia and New York (26). The etiological agents in the latter two studies were reported as F. solani and Fusarium sp., respectively, based on morphological species recognition.…”
Section: Resultsmentioning
confidence: 99%
“…Multilocus phylogenetic species recognition of medically important fusaria and important veterinary fusaria based on genealogical exclusivity (13) has revealed that approximately three-fourths of clinically relevant Fusarium species cannot be identified using phenotypic data (see reference 12 and references therein). To date, only a relatively small number of Fusarium strains from veterinary sources have been included in multilocus molecular phylogenetic studies, and they comprised 17 phylogenetically distinct species distributed among six species complexes, i.e., Fusarium incarnatum-equiseti, Fusarium chlamydosporum, Fusarium sambucinum, Fusarium oxysporum, Fusarium fujikuroi, and F. solani (12,(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%